Mating- and oviposition-dependent changes of the spermatheca and colleterial glands in the pest termite Cryptotermes brevis (Blattaria, Isoptera, Kalotermitidae) - da Silva, Iago Bueno [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Springer Nature, 2024)
The spermatheca and colleterial glands of female insects are organs associated with the reproductive system, responsible for sperm storage and secretion of egg coverings, respectively. Here we compared the development, secretory activity, and chemical nature of the secretion in the spermatheca and colleterial glands of different-aged females of the drywood termite Cryptotermes brevis. We also provide the ultrastructure of these organs in alate females. These structures have been poorly investigated in termites when compared to other eusocial insects (Hymenoptera) and termite-related dictyopterans (mantises and cockroaches). The spermatheca of C. brevis comprises a cone-shaped structure, connected to the genital chamber by a short duct. The colleterial glands, in turn, are divided into anterior and posterior tubules, each showing a basal trunk, and join into a common duct. Histological and histochemical analyses showed that the secretion of proteins and polysaccharides by the spermatheca takes place before pairing, but increases as females mate and store sperm. Colleterial glands of alates showed non-synchronous secretory activity, but the synthesis of products increased in egg-laying queens, together with the epithelium height. Ultrastructure of the spermatheca and colleterial glands revealed epithelia composed of class III secretory cells. Richness of mitochondria and electron-dense secretion in the spermatheca indicates synthesis and transport of content. Presence and absence of colleterial gland secretion in different individuals may reflect variable maturation stages of the females and secretory cells. Assuming that termites are iteroparous, the development and secretion of the spermatheca and colleterial glands play a crucial role for C. brevis queens.
Keywords: Exocrine glands; Oviposition; Pest species; Reproduction; Sperm storage; Ultrastructure